2002
DOI: 10.1023/a:1014791327253
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Biodegradable hydrophilic gelatin nanoparticles, containing different initial amounts of methotrexate (MTX), were prepared using a simple solvent evaporation technique based on a single water-in-oil emulsion and stabilized by the use of glutaraldehyde as cross-linking agent. The effects of several parameters on particle size, drug encapsulation efficiency and drug release were investigated. Size and shape of the nanoparticles were examined by scanning electron microscopy. The release of MTX was monitored in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(41 citation statements)
references
References 8 publications
1
40
0
Order By: Relevance
“…The increase in the yield with increasing PLGA and PVA concentrations could be explained by the greater stabilizing property of PVA during the emulsification process, which will enhance stabilization of the globules and formation of more particles. 35,36 The high PLGA concentration means viscous solutions, leading to larger and denser particles being produced, and this will subsequently increase the yield. The increase in the yield with PVA, PLGA concentrations, and homogenization speed observed in this research work correlates with those reported by Mao and colleagues, who reported an increase in the yield from 77% to 83% with an increasing PLGA concentration from 8% to 32%.…”
Section: Studentized Residualsmentioning
confidence: 99%
“…The increase in the yield with increasing PLGA and PVA concentrations could be explained by the greater stabilizing property of PVA during the emulsification process, which will enhance stabilization of the globules and formation of more particles. 35,36 The high PLGA concentration means viscous solutions, leading to larger and denser particles being produced, and this will subsequently increase the yield. The increase in the yield with PVA, PLGA concentrations, and homogenization speed observed in this research work correlates with those reported by Mao and colleagues, who reported an increase in the yield from 77% to 83% with an increasing PLGA concentration from 8% to 32%.…”
Section: Studentized Residualsmentioning
confidence: 99%
“…Well-established techniques are the desolvation, [33][34][35][36][37] the coacervation, [38][39][40] and water-in-oil emulsion techniques. [41][42][43] The flexibility offered by these techniques in tailoring the properties of the nanoparticles is limited. With increasing gelatin concentration and by using a gelatin with a broad molecular-weight distribution, it is not possible to effectively and uniformly achieve high gelatin content within the particles.…”
Section: Synthetic Possibilities By the Use Of Miniemulsionsmentioning
confidence: 99%
“…Moreover, secondary concerns include the toxicity of the protein vehicle itself, toxicity of its byproducts stemming from enzymatic degradation, and the clearance kinetics of the protein-drug complex in competition with the kinetics of accumulation due to the EPR effect. Notable examples of small molecules benefiting from this modality are doxorubicin [27, 2936], paclitaxel [3741], methotrexate [42–45], and curcumin [46, 47]. In addition, the strategy of delivering prodrug forms of such molecules has been invoked in tandem with the application of protein-based delivery vehicles – a testament to the high degree of engineering demanded of the challenge of drug delivery [35, 4850].…”
Section: Small Molecule Therapeuticsmentioning
confidence: 99%
“…Methotrexate can also be readily entrapped in emulsions of gelatin to form nanoparticles of 100–200 nm in diameter, which may be further stabilized by cross-linking with glutaraldehyde, and behave as depots for sustained loading and release [42]. Cascone et al have demonstrated a methotrexate release from gelatin nanoparticles over the course of 80+ hours determined by side diffusion chamber studies [42]. …”
Section: Small Molecule Therapeuticsmentioning
confidence: 99%